Psoriasis - Griffiths, Chris (Henry Stewart Talks, 2015)
Psoriasis, Demographics, Impact of psoriasis on mental health, Clinical features of psoriasis, Morphology, Immunology, Genetics, Comorbidities in psoriasis patients, Key cells and mechanisms in psoriasis, Evolving concepts in psoriasis pathophysiology, Psoriasis phenotypes, Treatment options for psoriasis, Current management, Future management, Cytokine targets in psoriasis, Biologic era for psoriasis: infliximab, Anti-IL-17 approaches for psoriasis, Stratified medicine